2018
DOI: 10.1159/000488652
|View full text |Cite
|
Sign up to set email alerts
|

Overstaging: A Challenge in Rectal Cancer Treatment

Abstract: Background: Preoperative staging, including computed tomography (CT), magnetic resonance imaging (MRI), and endoscopic ultrasound (EUS), is decisive to envisage the therapeutic concept for rectal cancer (RC). Overstaging may subject the patient to neoadjuvant therapy that does not improve survival but may lead to therapy-associated morbidity. Methods: This study retrospectively compares and values EUS, CT, and MRI in Union Internationale Contre le Cancer (UICC) stage I-III RC with a focus on overstaging. RC pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
2
22
1
Order By: Relevance
“…However, unfortunately none of the trials included in the current analysis provided sufficiently detailed information in their reports to perform this subgroup analysis. Nevertheless, this subgroup analysis would have been of particular importance because of the frequent problem of clinical overstaging in rectal cancer, which may result in unnecessary, ineffective, and even harmful overtreatment (53).…”
Section: Reviewmentioning
confidence: 99%
“…However, unfortunately none of the trials included in the current analysis provided sufficiently detailed information in their reports to perform this subgroup analysis. Nevertheless, this subgroup analysis would have been of particular importance because of the frequent problem of clinical overstaging in rectal cancer, which may result in unnecessary, ineffective, and even harmful overtreatment (53).…”
Section: Reviewmentioning
confidence: 99%
“…Despite the recent technical improvements, all imaging modalities are still at risk of staging failure, with an overstaging rate reported up to 30% [ 22 , 23 , 24 ]. Numerous studies have reported on MRI and ERUS diagnostic performance for rectal cancer staging, but there are considerable differences in methodologic analysis, results and accuracy measures among them, particularly for T3 staging [ 4 , 22 , 24 , 25 , 26 , 27 ]. Moreover, none of the studies have been performed using three different imaging modalities in comparison and focused on a single stage of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although analyzing overstaging was not the aim of the analysis, Table 2 shows it does occur. Although the numbers are small, due to the neoadjuvant therapies that hamper analyses on overstaging, it is a problem discussed in literature 38,39 . Overstaging can lead to unnecessary neoadjuvant treatment that might not offer a benefit, but does do harm.…”
Section: Discussionmentioning
confidence: 99%
“…Although the numbers are small, due to the neoadjuvant therapies that hamper analyses on overstaging, it is a problem discussed in literature. 38,39 Overstaging can lead to unnecessary neoadjuvant treatment that might not offer a benefit, but does do harm. Short-course radiotherapy is associated with more frequent fecal incontinence, sexual problems, and delayed wound healing.…”
Section: Multivariable Analysis Revealed That For Patients With (Y)pn1mentioning
confidence: 99%